2017
DOI: 10.1158/1078-0432.ccr-16-1432
|View full text |Cite
|
Sign up to set email alerts
|

Ipilimumab with Stereotactic Ablative Radiation Therapy: Phase I Results and Immunologic Correlates from Peripheral T Cells

Abstract: Purpose Little prospective data is available on clinical outcomes and immune correlates from combination radiation and immunotherapy. We conducted a phase I trial (NCT02239900) testing stereotactic ablative radiation therapy (SABR) with ipilimumab. Experimental Design SABR was given either concurrently (1 day after the first dose) or sequentially (1 week after the second dose) with ipilimumab (3 mg/kg every 3 weeks for 4 doses) to 5 treatment groups: concurrent 50 Gy (in 4 fractions) to liver; sequential 50 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
235
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 273 publications
(250 citation statements)
references
References 35 publications
4
235
0
4
Order By: Relevance
“…Clinical studies revealed that the recommended dose of ipilimumab in phased combination with chemotherapies was identified as 10 mg/kg and had a better treatment benefit in combination with chemotherapeutic agents, such as carboplatin, etoposide and paclitaxel in patients with lung cancer [94][95][96] and advance melanoma [97,98]. Moreover,combining radiotherapy and ipilimumab was feasible and well tolerated with limited toxicity for solid tumors [99]. The report showed that radiation with doses ranged from 45-61.2 Gy in patients with stage IIIA NSCLC after 3 cycles of neo-adjuvant chemotherapy including ipilimumab with the last two cycles was well tolerated with no observed grade≥3 toxicity including NSCLC [100].In patients with metastatic castrationresistant prostate cancer, the combination of ipilimumab with radiotherapy (8Gy/lesion, up to 3 lesions) showed synergistic antitumor activity with disease control and manageable adverse effects [101].In addition, the efficacy of ipilimumab with other immunotherapies was evaluated in a number of clinical trials.…”
Section: Combination With Other Therapiesmentioning
confidence: 99%
“…Clinical studies revealed that the recommended dose of ipilimumab in phased combination with chemotherapies was identified as 10 mg/kg and had a better treatment benefit in combination with chemotherapeutic agents, such as carboplatin, etoposide and paclitaxel in patients with lung cancer [94][95][96] and advance melanoma [97,98]. Moreover,combining radiotherapy and ipilimumab was feasible and well tolerated with limited toxicity for solid tumors [99]. The report showed that radiation with doses ranged from 45-61.2 Gy in patients with stage IIIA NSCLC after 3 cycles of neo-adjuvant chemotherapy including ipilimumab with the last two cycles was well tolerated with no observed grade≥3 toxicity including NSCLC [100].In patients with metastatic castrationresistant prostate cancer, the combination of ipilimumab with radiotherapy (8Gy/lesion, up to 3 lesions) showed synergistic antitumor activity with disease control and manageable adverse effects [101].In addition, the efficacy of ipilimumab with other immunotherapies was evaluated in a number of clinical trials.…”
Section: Combination With Other Therapiesmentioning
confidence: 99%
“…We therefore established animal models of mesothelioma in mice to assess the interaction of radiation and the immune system using a non-ablative short course of hypofractionated radiation such as 15 Gy in 3 fractions (9,27). When this type of radiation is delivered to the primary tumor, tumorassociated antigens (Ag) are released from dead tumor cells and then processed by antigen presenting cells (APC) such as DCs.…”
Section: Radiation and Immunotherapy In Mesotheliomamentioning
confidence: 99%
“…Local radiation resulted in an increase of tumor-infiltrating T cells, while CTLA-4 blockade led to significant reduction of Tregs and increase of CTLs in both tumors. The abscopal effect was enhanced by targeting the immune checkpoints through modulation of T cell immune response in murine mesothelioma (9).…”
Section: Radiation and Immunotherapy In Mesotheliomamentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore the role of immunotherapy for SCLC, our department is conducting an investigator-initiated phase I study to assess the effects of pembrolizumab and radiation in extensive and limited stage disease (NCT02402920). The rationale behind such a treatment paradigm is that radiation releases antigens, providing greater immune system access to the array of somatic mutations inherent in this disease (18,19).…”
mentioning
confidence: 99%